2022
DOI: 10.3389/fendo.2022.981317
|View full text |Cite
|
Sign up to set email alerts
|

Using human urinary extracellular vesicles to study physiological and pathophysiological states and regulation of the sodium chloride cotransporter

Abstract: The thiazide-sensitive sodium chloride cotransporter (NCC), expressed in the renal distal convoluted tubule, plays a major role in Na+, Cl- and K+ homeostasis and blood pressure as exemplified by the symptoms of patients with non-functional NCC and Gitelman syndrome. NCC activity is modulated by a variety of hormones, but is also influenced by the extracellular K+ concentration. The putative “renal-K+ switch” mechanism is a relatively cohesive model that links dietary K+ intake to NCC activity, and may offer n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 162 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, in those studies that investigated a specific mRNA of uEVs in endocrine hypertension, namely NCC in PA and 11β-HSD2 in AME ( 9 , 15 ), the results were somewhat different from those expected when looking at the specific protein studies. Previous data on uEVs NCC protein demonstrated that patients with PA are characterized by a higher level of NCC and pNCC in comparison to essential hypertensive patients, with a modulation by both mineralocorticoid administration and potassium levels, and a higher abundance in patients with documented monolateral versus bilateral PA disease ( 16 , 17 , 20 , 23 ). Consistent with these findings, one could expect a reflection of the differences in protein abundance in the abundance of the corresponding mRNA, but this did not occur.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, in those studies that investigated a specific mRNA of uEVs in endocrine hypertension, namely NCC in PA and 11β-HSD2 in AME ( 9 , 15 ), the results were somewhat different from those expected when looking at the specific protein studies. Previous data on uEVs NCC protein demonstrated that patients with PA are characterized by a higher level of NCC and pNCC in comparison to essential hypertensive patients, with a modulation by both mineralocorticoid administration and potassium levels, and a higher abundance in patients with documented monolateral versus bilateral PA disease ( 16 , 17 , 20 , 23 ). Consistent with these findings, one could expect a reflection of the differences in protein abundance in the abundance of the corresponding mRNA, but this did not occur.…”
Section: Discussionmentioning
confidence: 97%
“…Besides lipids and proteins, uEVs also carry RNA molecules and are secreted from renal epithelial cells into the urine, thus providing access to information about kidney tissue physiology and possibly to kidney-related diseases pathophysiology ( 21 , 22 ). Most studies, however, have focused, on the proteins and non-coding RNA profiles of uEVs and almost all are related to endocrine hypertension referring more specifically to primary aldosteronism (PA) and to apparent mineralocorticoid excess (AME) ( 12 14 , 16 , 17 , 19 , 20 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the uEV-to-UCr ratio may be considered as a housekeeper indicating the stage of DN. uEVs may be non-invasive biomarkers in predicting and monitoring the progression of renal physiological and pathological conditions (38,39). More and more evidence have established a valuable role of uEVs in renal physiology and pathology (38,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the uEV-to-UCr ratio may be considered as a housekeeper indicating the stage of DN. uEVs may be non-invasive biomarkers in predicting and monitoring the progression of renal physiological and pathological conditions ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs feature in renal physiology and are widely involved in the occurrence and progression of various kidney diseases. It can be used for the diagnosis of kidney diseases and be instrumental in the treatment of renal diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%